Pengembangan Model Ilmu-Ilmu Kemanusiaan di Institut Teknologi Bandung Kontribusi Ilmu-Ilmu Kemanusiaan Berbasis Teknologi dalam Mendukung Pembangunan Nasional Berkelanjutan - Miftah Faridl (Jurnal Sosioteknologi, 2007)
As far as the discovering of the relevant model for developing humanities and social science for ITB, this study employed the survey descriptive "“ evaluative method. The method was used to explore the stakeholders' perception concerning what they need, how to cope with the needs, who does what, for whom something is done, and what risks will result from what is done. Based on the data analysis on the stakeholders' perception, it was found that the subjects in the curriculum of every study program in ITB, including the subjects taught by the expert group, had not yet successfully contributed to the production of ITB graduates that can play their role as the agents of change. In addition, the interviews with the ITB students showed that the subjects that they needed were the subjects that could help them apply what they have learned as well as could help them contribute to the national development. It was found that the subjects that they needed were the subjects which could help them to do an effective communication, to participate in a teamwork, to acquire autonomous qualities, and to attain entrepreneur traits. Based on the above-mentioned findings, developing the humanities, life science, and social science for ITB should therefore be based on the epistemology that can fashion ITB students to be a group of people that have moral integrity, communication skills, team work capabilities, opportunity-creating abilities, self-potency development skills, and soft skills. Key words: Moral Integrity, Communication skills, cultural network skills, self-potential development skills, entrepreneurship